Enhancing the hot-corrosion resistance of atmospheric plasma sprayed Ni-based coatings by adding a deoxidizer - Dong, Xin-Yuan; Luo, Xiao-Tao; Ge, Yi; Li, Chang-Jiu (Materials & design, 2021)
[Display omitted] •The generation of ultra-high temperature droplets benefits the suppression of the in-flight oxidation of boron-alloyed NiCr particles during plasma spraying.•Ni20Cr4B coating with a low and constant oxygen content of 0.18 wt.% was deposited in open atmosphere by plasma spraying.•The limited oxide inclusion in coating leads to deposition of highly dense coating with a porosity of 0.21%.•The highly dense microstructure of Ni20Cr4B coating blocks the penetration of corrosive media in hot corrosion test with molten salts. Atmospheric plasma sprayed metallic coatings always contain oxides because of the entrainment of ambient air into plasma jet, which significantly limits their performances and applications. This paper presents an approach to deposit highly dense Ni-based alloy coatings with oxide-free particles achieved by introducing boron as deoxidizer element through plasma spraying to generate ultrahigh temperature Ni20Cr4B droplets. During spraying, boron is preferentially oxidized and the formed B2O3 is completely removed due to rapid evaporation. Thus, the in-flight oxidation of metal can be suppressed to achieve oxide-free particles. The oxygen content of plasma sprayed Ni20Cr4B coating is lower than 0.18 wt.% and presents little change over a wide spray distance range from 60 mm to 140 mm. With such a low oxygen content, the Ni20Cr4B coating presents a highly dense microstructure (porosity of 0.21 ± 0.11%) and well-bonded inter-splat interfaces. The hot-corrosion test at 600 °C for 200 h shows that the highly dense Ni20Cr4B coating can effectively block the penetration of the corrosion media and the corrosion only takes place at the coating surface, while severe inner corrosion was observed for the traditional Ni20Cr coating with poor inter-splat bonding.